Python basics : a self-teaching introduction - Bhasin, Harsh (Mercury Learning and Information, 2019)
Offering in-depth treatment of topics such as classes, inheritance, BST, and NumPy, this book is designed for use as a primary introduction to Python and can be used as an introductory text or as a resource for professionals in industry. --